STATE POLICY IN HEALTH PROTECTION OF CHILDREN: PROBLEMS AND TASKS - T.V. Yakovleva; A.A. Baranov ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):6-11)